Untapped rich microbiota of mangroves of Pakistan: diversity and community compositions - Bushra, Rabia; Ahmed, Iftikhar; Li, Jia-Ling; Lian, Zhenghan; Li, Shuai; Ali, Ahmad; Uzair, Bushra; Amin, Arshia; Ehsan, Muhammad; Liu, Yong-Hong; Li, Wen-Jun (Folia microbiologica, 2024)
The mangrove ecosystem is the world's fourth most productive ecosystem in terms of service value and offering rich biological resources. Microorganisms play vital roles in these ecological processes, thus researching the mangroves-microbiota is crucial for a deeper comprehension of mangroves dynamics. Amplicon sequencing that targeted V4 region of 16S rRNA gene was employed to profile the microbial diversities and community compositions of 19 soil samples, which were collected from the rhizosphere of 3 plant species (i.e., Avicennia marina, Ceriops tagal, and Rhizophora mucronata) in the mangrove forests of Lasbela coast, Pakistan. A total of 67 bacterial phyla were observed from three mangroves species, and these taxa were classified into 188 classes, 453 orders, 759 families, and 1327 genera. We found that Proteobacteria (34.9-38.4%) and Desulfobacteria (7.6-10.0%) were the dominant phyla followed by Chloroflexi (6.6-7.3%), Gemmatimonadota (5.4-6.8%), Bacteroidota (4.3-5.5%), Planctomycetota (4.4-4.9%) and Acidobacteriota (2.7-3.4%), Actinobacteriota (2.5-3.3%), and Crenarchaeota (2.5-3.3%). After considering the distribution of taxonomic groups, we prescribe that the distinctions in bacterial community composition and diversity are ascribed to the changes in physicochemical attributes of the soil samples (i.e., electrical conductivity (ECe), pH, total organic matter (OM), total organic carbon (OC), available phosphorus (P), and extractable potassium (CaCO3). The findings of this study indicated a high-level species diversity in Pakistani mangroves. The outcomes may also aid in the development of effective conservation policies for mangrove ecosystems, which have been hotspots for anthropogenic impacts in Pakistan. To our knowledge, this is the first microbial research from a Pakistani mangrove forest.
Keywords: Soil Microbiology; mokřady; Pákistán; RNA, Ribosomal, 16S; rhizosféra; DNA, Bacterial; Metabarcoding; Bacteria; Mangroves; biodiverzita; Illumina sequencing; Proteobacteria; Microbiota; DNA bakterií; mikrobiota; Wetlands; Rhizophoraceae; Pakistan; RNA ribozomální 16S; půdní mikrobiologie; fylogeneze; Microbial diversity; Rhizosphere; Avicennia; Biodiversity; Phylogeny